Hospitality revenue management : concepts and practices - Szende, Peter (Palm Bay, Florida, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL ; Abingdon, Oxon : CRC Press, 2021)
"This new textbook, Hospitality Revenue Management: Concepts and Practices, provides a comprehensive, in-depth introduction to the basic concepts and best practices of hospitality revenue management. With a real-world, hands-on approach, the book places students in the role of a revenue manager striving to succeed in an ever-changing hospitality business environment. The book takes a unique multi-author, collaborative approach, with chapters from outstanding industry leaders who share their experience and provide the information necessary to arm students with the most up-to-date tools and methods they to be effective in the hospitality revenue management field. The chapters cover the important topics in hospitality revenue management, including hotel pricing, hotel segmentation, distribution channels, competitive analysis, hotel forecasting, performance analysis, market data, supply and demand management, and more. This comprehensive and contemporary textbook effectively meets the curricular requirements of undergraduate and graduate courses. The book can also be used as a reference for practitioners and as a text for executive education programs. Each chapter includes features to keep students interested and engaged. These include case studies, internet activities, team projects, spreadsheet assignments, brief histories, and more."--
Hotel Revenue Management: an Introduction / Carolyn Fredey and Roy Madhok -- The Fundamentals of Pricing Hotel Guest Rooms / Carolyn Fredey and Raul Moronta -- Evolving Hotel Segmentation / Roy Madhok and Theresa Doherty -- Key Hotel Distribution Channels / Elyana Falk and Calvin Anderson -- Competitive Analysis in Hotel Revenue Management / Theresa Doherty and Leslie Lew -- Hotel Revenue Forecasting and Budgeting / Theresa Doherty and Carolyn Fredey -- Performance Analysis in Hotel Revenue Management / Roy Madhok and Leslie Lew -- Market Data for Hotel Revenue Management / Calvin Anderson, Elyana Falk, and Nicholas Catalfamo -- Restaurant Revenue Management: Basic Concepts / Kristin V. Rohlfs -- Restaurant Revenue Management: Advanced Demand Management Concepts / Kristin V. Rohlfs -- Restaurant Revenue Management: Advanced Supply Management Concepts / Kristin V. Rohlfs -- Function Space Optimization / Marianna Accomando and Bob Chamberlin -- Cruise Revenue Management / Adam Snitzer -- Total Revenue Management / Gabor Fenyves -- Revenue Management: Hotel Owner's Perspective / Jonathan Jaeger and Lambis Pahiyiannakis.
OCLC-licensed vendor bibliographic record.
Keywords: Revenue management; Hotel management; Hospitality industry -- Management; BUSINESS & ECONOMICS / Accounting / Managerial; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Economics / General